2021
DOI: 10.1038/s41598-021-89760-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of respiratory large droplet production during common airway procedures using high-speed imaging

Abstract: During the COVID-19 pandemic, a significant number of healthcare workers have been infected with SARS-CoV-2. However, there remains little knowledge regarding large droplet dissemination during airway management procedures in real life settings. 12 different airway management procedures were investigated during routine clinical care. A high-speed video camera (1000 frames/second) was for imaging. Quantitative droplet characteristics as size, distance traveled, and velocity were computed. Droplets were detected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Since it is common for patients to speak or cough during otoscopy and sonography, subjects were saying aloud the phrase “Stay healthy” and afterwards coughed once within a measuring cycle to simulate the worst-case scenario. The phrase was chosen for its benchmark status [ 14 , 29 ]. For the whole tasks, two cycles of “Stay healthy” and coughing were executed by each subject.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it is common for patients to speak or cough during otoscopy and sonography, subjects were saying aloud the phrase “Stay healthy” and afterwards coughed once within a measuring cycle to simulate the worst-case scenario. The phrase was chosen for its benchmark status [ 14 , 29 ]. For the whole tasks, two cycles of “Stay healthy” and coughing were executed by each subject.…”
Section: Methodsmentioning
confidence: 99%
“…The measuring principle for the droplet experiments was analogue to Mueller et al (2021) [ 29 ] with an optimized stationary setup shown in Figure 1 . Subjects were recorded in front of a professional black photography background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inspired by the habit of sweeper fishes in the aquarium to attach to rocks and glass to stabilize the body, the authors attached these cell membranes on inhaled microfluidic hydrogel microspheres to improve their accumulation in the respiratory system. Since the deposition site of microspheres is determined by their aerodynamic diameter (Dare) in the respiratory system, 8 for the “sweeper” system to work, the authors must precisely control the Dare of microspheres at 7.89, 6.63, and 4.21 μm. In this way, these microspheres accumulated in the oropharynx, upper airway, and lower airway of the lung lobes, leading to the protection of the whole respiratory tract against the virus and potentially reducing the viral transmission in humans.…”
Section: Main Textmentioning
confidence: 99%
“…From the early days of the coronavirus disease 2019 (COVID-19) pandemic to much of 2020, the World Health Organization (WHO) strongly believed that severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2), the virus responsible for COVID-19, primarily spreads through larger respiratory droplets expelled by infected individuals while coughing, sneezing, or speaking 1 – 4 . However, reports of numerous airborne transmission possibilities have emerged, including outbreaks at the Wuhan hospital 5 and a restaurant in Guangzhou 6 9 .…”
Section: Introductionmentioning
confidence: 99%